PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR ASET, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Elvira, Shannen; Rasyid, Rosmita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research was conducted to find out how profitability, liquidity, asset structure, and company size affect companyvalue in companies in the consumer non cyclicals sector and the healthcare sector that are listed on the Indonesia Stock Exchange during 2019–2021. The samples selected by the purposive sampling method and valid data were 39 companies, consisting of 31 companies in the consumer non cyclicals sector and 8 companies in the healthcare sector. Techniques for data processing involving multiple regression analysis and the use of tools, specifically the Eviews program version 12.0 and Microsoft Excel 2010. The results of this study indicate that profitability and asset structure have a positive effect on firm value. Liquidity and firm size have no effect on firm value.